Factors Associated with Student Achievement at Pgri Junior High School Pekanbaru City During the Covid-19 Pandemic in 2022: Faktor-Faktor Yang Berhubungan Dengan Prestasi Belajar Siswa Di Sekolah Menengah Pertama Pgri Kota Pekanbaru Pada Masa Pandemi Covid-19 Tahun 2022 - Tiara Alisa Putri; Alhidayati Alhidayati; Yuyun Priwahyuni; Ikhtiyaruddin Ikhtiyaruddin; Winda Septiani (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Learning achievement is the result of learning. Achievement is obtained from evaluation or assessment. Each child will have different learning outcomes or achievements from one another. The purpose of this study was to determine the factors related to student achievement at the PGRI Junior High School in Pekanbaru City during the COVID- 19 pandemic in 2022. This research method uses quantitative with a cross sectional.This research will be conducted at SMP PGRI Pekanbaru City with a total sample of 98 respondents using a total sampling technique. Data analysis used univariate and bivariate with chi-square (α=0.05). This research was carried out in July 2022. Based on the results of the research, the conclusion shows that the proportion of students who have poor academic achievement during the COVID- 19 pandemic in 2022 is 56.1%. The determinant that has a relationship between learning achievement and attitude (Pvalue = 0.010) with 95% POR = 3.680 (1.442-9.390), the effect of using gadgets(Pvalue = 0.005) with 95% POR = 3.818(1.566-9.308),peer influence (Pvalue = 0.002) with 95% por = 4.081% (1.717-9.698), the role of parents (Pvalue = 0.000) with 95% POR = 8.800(3.495-22.157) and the role of the teacher (P-value = 0.009) with 95% POR = 3.368 (1,436-7,901). It is recommended to the school, especially for Guidance Counseling (BK) teachers, are expected to always provide a strong attitude of learning motivation to students in order to improve their achievement in learning.